ADAPTASI USAHA MIKRO KECIL MENEGAH (UMKM) DIMASA PADEMI COVID-19 - Barisa, Wildan (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
In March 2020, Indonesia is experiencing a Covid-19 pandemic, not only Indonesia, but almost the entire world that has experienced the Covid-19 pandemic. Appeals to prevent the spread of this virus, people must stay at home. This has an impact on an unstable economy, including UMKM/MSME players. Therefore. However, all problems can be resolved with several policies an Adaptation strategy is needed for MSME players so that they can maintain their business during the Covid-19 pandemic. In this study the authors used descriptive qualitative research methods. The results of this study there are 2 MSME actors who are wholesalers, and retailers, they adapt in ways that the wholesaler reduces the supply of goods. Retail traders still supply the same number of goods before the pandemic, because these traders did not really have an impact on the Covid-19 pandemic. The results of this study are important to be understood by MSME actors for wholesalers, and is expected to always be responsive to environmental changes. Keywords: UMKM, Adaptation, and policies